2019
DOI: 10.3310/hta23560
|View full text |Cite
|
Sign up to set email alerts
|

A support package for parents of excessively crying infants: development and feasibility study

Abstract: Background Around 20% of 1- to 4-month-old infants cry for long periods without an apparent reason. Traditionally, this was attributed to gastrointestinal disorder (‘colic’), but evidence shows that just 5% of infants cry a lot because of organic disturbances; in most cases, the crying is attributable to normal developmental processes. This has led to a focus on the impact of the crying on parents. Parental vulnerabilities influence how parents evaluate and respond to the crying and predict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
2
18
0
1
Order By: Relevance
“…29 In another study, assisting parents who sought help because of excessive infant crying with a support package not only led to reductions in reported crying, but was also associated with substantial reductions in parental frustration, anxiety, depression and contact with professionals. 30 Our findings suggest that we might want to intervene differently for mothers and fathers with an excessively crying infant. Integrated care which reduces negative feelings of stress and bonding in mothers might also have positive effects on these feelings in fathers.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…29 In another study, assisting parents who sought help because of excessive infant crying with a support package not only led to reductions in reported crying, but was also associated with substantial reductions in parental frustration, anxiety, depression and contact with professionals. 30 Our findings suggest that we might want to intervene differently for mothers and fathers with an excessively crying infant. Integrated care which reduces negative feelings of stress and bonding in mothers might also have positive effects on these feelings in fathers.…”
Section: Discussionmentioning
confidence: 83%
“…In one study, family‐based treatment reduced the amount of crying faster than did standard paediatric care 29 . In another study, assisting parents who sought help because of excessive infant crying with a support package not only led to reductions in reported crying, but was also associated with substantial reductions in parental frustration, anxiety, depression and contact with professionals 30 …”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that interventions targeting overall parenting are effective in helping children with regulatory problems and their parents [ 5 , 12 ]. Reported effects are reduced parental frustration anxiety, reported amount of infant crying, more contact with health professionals and increased knowledge about crying [ 30 ]. As described, the differences between the groups in this study are significant, but also moderate to small over time.…”
Section: Discussionmentioning
confidence: 99%
“…The gastrointestinal causes of colic are often referred to as developmental lactose intolerance, altered gut microorganism, immaturity of the gut, increased motilin receptors, or cow milk hypersensitivity [ 32 ]. Yet, research has shown that gastrointestinal disturbances only apply to a minority (5%) of infants who cry excessively during the first months of life [ 5 , 30 ]. Still, it is important to be aware that the term colic is used as a collective term for excessive infant crying and fussing.…”
Section: Discussionmentioning
confidence: 99%
“…27 Excessive crying in infants is a challenge. 29 Identifying the cause of Excessive Crying in Children with Cerebral Palsy and Communication De cits [ECCCPCD], either because of their age or global developmental delay/profound intellectual retardation, is more challenging. It is di cult to distinguish discomfort, pain, and distress in such children.…”
Section: A Introductionmentioning
confidence: 99%